Rootstocks: Diversity, Domestication, and Impacts on Shoot Phenotypes. (May 2016) - Warschefsky, Emily J.; Klein, Laura L.; Frank, Margaret H.; Chitwood, Daniel H.; Londo, Jason P.; von Wettberg, Eric J.B.; Miller, Allison J.
Abstract : Grafting is an ancient agricultural practice that joins the root system (rootstock) of one plant to the shoot (scion) of another. It is most commonly employed in woody perennial crops to indirectly manipulate scion phenotype. While recent research has focused on scions, here we investigate rootstocks, the lesser-known half of the perennial crop equation. We review natural grafting, grafting in agriculture, rootstock diversity and domestication, and developing areas of rootstock research, including molecular interactions and rootstock microbiomes. With growing interest in perennial crops as valuable components of sustainable agriculture, rootstocks provide one mechanism by which to improve and expand woody perennial cultivation in a range of environmental conditions. Trends: As concerns mount about food security in a changing climate, attention is refocusing on perennial crops as important components of sustainable agriculture. In many economically important woody perennial crops (e.g., many Rosaceae, Citrus, and grapes), a fruit-bearing shoot (scion) is grafted to a root system (rootstock) that is genetically distinct from the scion. Rootstocks are selected for rooting and grafting capacity, abiotic and biotic stress tolerance, and their ability to beneficially alter scion phenotypes. Relatively little is known about the diversity of rootstocks used for any given crop, the geographic origins or current distribution of cultivated rootstocks, or their domestication. A common scion can be grafted to segregating rootstock populations to produce a genetic map of both the traits of the rootstocks themselves and their effects on scion phenotype.